The rock climber´s exercise guide. Training for strength, power, endurance, flexibility, and stability - Hörst, E. (FALCON, 2017)
Rock climbing is one of the most physically challenging sports, testing strength, endurance, flexibility, and stamina. Good climbers have to build and maintain each of these assets. This revised and updated edition of the classic book, Conditioning for Climbers, provides climbers of all ages and experience with the knowledge and tools to design and follow a comprehensive, personalised exercise program.